Outcomes of open government: Does an online platform improve citizens' perception of local government?. Issue 5 (14th January 2019) - Schmidthuber, Lisa; Stütz, Simone; Hilgers, Dennis
Abstract : Purpose: Governments all over the world have implemented citizensourcing initiatives to integrate citizens into decision-making processes. A more participative decision-making process is associated with an open government and assumed to benefit public service quality and interactive value creation. The purpose of this paper is to highlight the outcomes of open government initiatives and ask to what extent open government participation is related to perceived outcomes of open government. Design/methodology/approach: Data conducted from a survey among users of a citizensourcing platform and platform data are used to perform non-parametric analyses and examine the relationship between platform participation and perceived outcomes of open government. Findings: The findings of this paper suggest that active platform usage positively relates to several outcomes perceived by citizens, such as improved information flow, increased trust in and satisfaction with local government. In contrast, repetitive participation does not significantly relate to users' outcome evaluation. Practical implications: This study suggests public managers to provide possibilities for citizen participation and interaction with government such as citizensourcing initiatives. In particular, it recommends promoting participants' platform activity, as proactive platform participation has positive effects on perceived outcomes of open government. Originality/value: Previous literature discussed what it needs to realize a transparent and participatory government. First empirical studies deal with government institutions' reasons to promote exchange with citizens, and investigate citizens' motivation to participate in citizensourcing activities, but have disregarded the consequences of open government so far. This study thus provides first insights into the outcomes of open government, as perceived by the users.